Micro electro discharge machining of non-conductive ceramic - Ali, Mohammad Yeakub; Maleque, Md. Abdul; Banu, Asfana; Sabur, Abdus; Debnath, Sujan (Trans Tech Publications, 2018)
Electro discharge machining (EDM) as a die sinking process has taken off in 1943. Since then it was known as a non-conventional machining process and its application was limited for processing only electrically conductive materials. Later on, due to the widespread applications, this EDM process is considered conventional as usual. However, in the recent years EDM has gone through considerable changes especially with dielectric fluids, simple to complex geometry, meso to micro sized structures, nanometric surface finish, and so on. In addition, the application of EDM has also been extended for processing electrically semi-conductive and non-conductive materials like ceramics and composites. This paper discussed micro electro discharge machining of non-conductive ceramic materials. It includes detail process development, modelling of material removal rate and surface finish which include the effect of multi spark and random spalling conditions.